Molecular Dynamics Validation of Crizotinib Resistance to ALK Mutations (L1196M and G1269A) and Identification of Specific Inhibitors. Issue 10 (18th May 2017) - Nagasundaram, Nagarajan; Wilson Alphonse, Carlton Ranjith; Samuel Gnana, Prakash Vincent; Rajaretinam, Rajesh Kannan
ABSTRACT: Anaplastic lymphoma kinase (ALK) positive non‐small cell lung cancer (NSCLC) patients are mostly treated with ALK tyrosine kinase inhibitors (TKIs). Crizotinib is the first generation ALK inhibitor practiced as a primary chemo to combat cancer cells followed by second generation inhibitor ceritinib which are effective against crizotinib resistant ALK mutations. However, patients treated with these drugs invariably relapsed because of the development of new drug resistance mutations. In this study we explored the crizotinib resistance in the presence of ALK mutations L1196M and G1269A through molecular dynamics simulation studies. Further mutation specific inhibitors CID 71748211 and CID 71728095 were identified to potentially inhibit ALK with mutations L1196M and G1269A, respectively. This computational investigation in‐sighted the molecular factors involved in crizotinib resistance which enhanced in the identification of new ALK drugs that brings individualized medicine to treat ALK positive NSCLC patients with specific mutations. J. Cell. Biochem. 118: 3462–3471, 2017. © 2017 Wiley Periodicals, Inc. Abstract : This computational investigation in‐sighted the molecular factors involved in crizotinib resistance which enhanced in the identification of new ALK drugs that bring individualized medicine to treat ALK positive NSCLC patients with specific mutations.